Combined application of green manure and straw mulch improves rice yield and mitigates methane emissions - Abdulkareem Raheem; Xichu Yu; Kailou Liu; Yan Wu; Aixing Deng; Zhenwei Song; Jun Zhang; Weijian Zhang (Soil Advances)
Rice paddies, a major agricultural source of greenhouse gas (GHG) emissions, require sustainable management to balance increasing grain demand with emissions reduction. Based on a 38-year experiment, this study investigates the combined effects of winter-planted green manure (Chinese milk vetch: Astragalus sinicus L.) and straw mulching on soil properties, rice yield, and GHG emissions in a double rice cropping system. The treatments were: 100 % NPK, reduced NPK with milk vetch (NPK+A), reduced NPK with milk vetch and straw (NPK+A+S), and no fertilizer (CK). Compared to CK, the NPK+A+S, NPK+A, and 100 % NPK treatments significantly improved total nitrogen, available potassium, and rice yields (p < 0.05). However, the annual methane (CH4) emissions were significantly increased by 162.0 % and 112.1 % in the treatments of 100 % NPK and NPK+A, respectively, but not NPK+A+S, relative to CK (p > 0.05). Notably, the NPK+A+S treatment significantly outperformed the 100 % NPK treatment, achieving a higher annual rice yield (11.61 t ha−1 vs. 10.77 t ha−1) and lower annual CH4 emissions (p < 0.05). No marked differences were observed in nitrous oxide (N2O) emissions among the treatments. Together, our findings suggest that the combined application of winter-grown milk vetch and straw mulch can improve rice yield, and reduce CH4 emissions.